2007
DOI: 10.1111/j.1529-8817.2006.00293.x
|View full text |Cite
|
Sign up to set email alerts
|

CYANIDIA (CYANIDIALES) POPULATION DIVERSITY AND DYNAMICS IN AN ACID‐SULFATE‐CHLORIDE SPRING IN YELLOWSTONE NATIONAL PARK1

Abstract: The unicellular eukaryotic algae Cyanidium, Galdieria, and Cyanidioschyzon (herein referred to as ''cyanidia'') are the only photoautotrophs occurring in acidic (pH<4.0) geothermal environments at temperatures above 401C. In Yellowstone National Park (YNP), we examined an annual event we refer to as ''mat decline,'' where cyanidial mats undergo a seasonably defined color fading. Monthly sampling of chemical, physical, and biological features revealed that spring aqueous chemistry was essentially invariant over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(51 citation statements)
references
References 48 publications
1
49
1
Order By: Relevance
“…or C. merolae in this one endolithic sample. In contrast, we did not detect any C. caldarium phylotypes through extensive culturing attempts from collections in YNP, Japan, and New Zealand, nor has C. caldarium been detected in 18S rDNA molecular surveys of Dragon Spring in Norris Geyser Basin (17) or in Nymph Creek (10), both in YNP. The paper by Walker et al (36) claims to have identified a cyanidial sequence closest to C. caldarium from an endolithic sample in the Norris Geyser Basin, but we believe this claim is in error (unpublished data).…”
Section: Discussioncontrasting
confidence: 81%
See 1 more Smart Citation
“…or C. merolae in this one endolithic sample. In contrast, we did not detect any C. caldarium phylotypes through extensive culturing attempts from collections in YNP, Japan, and New Zealand, nor has C. caldarium been detected in 18S rDNA molecular surveys of Dragon Spring in Norris Geyser Basin (17) or in Nymph Creek (10), both in YNP. The paper by Walker et al (36) claims to have identified a cyanidial sequence closest to C. caldarium from an endolithic sample in the Norris Geyser Basin, but we believe this claim is in error (unpublished data).…”
Section: Discussioncontrasting
confidence: 81%
“…In other work, we further checked the possibility that Galdieria morphotypes were contaminated with a few C. merolae type cells that might more readily rupture and release their DNA because of the lack of a cell wall, leading to the preferential amplification of their DNA. A culture of a Galdieria sulphuraria type II from YNP (CCMEE 5572), possessing a rigid cell wall, was mixed in various proportions with a "true" Cyanidioschyzon merolae morphotype (CCMEE 5610 4a Recently, we found that cpSSRs (or microsatellites) could be used to identify genetic differences among six cultured Galdieria-like type IA morphotypes that shared identical 18S rRNA gene sequences with C. merolae (17). Therefore, in the current study, we employed an approach similar to the above method to more closely examine these strains for evidence of genotypic variation.…”
Section: Figmentioning
confidence: 99%
“…Our results indicate that the distribution of hydA in YNP is non-random and is pH-dependent, suggesting a role for pH in the ecology and evolution of hydA in YNP. The pH-dependent distribution of hydA in YNP is similar to the distribution of phototrophs in YNP as evinced by the distribution of bchL/chlL genes where the upper temperature limit for oxygenic phototrophs in alkaline environments was observed to decrease from B70 1C in alkaline pH 9.0 systems to B48 1C in acidic pH 3.0 systems, a set of observations that are consistent with the qualitative trends noted in earlier studies (Cox and Shock, 2003;Spear et al, 2005;Lehr et al, 2007). The relationship between the presence of hydA and bchL/chlL could be explained, in part, by the temporal dynamics of phototrophic mat communities, which cycle from oxygen saturation during the day to anoxia at night (Revsbech and Ward, 1984).…”
Section: Discussionsupporting
confidence: 87%
“…In acidic environments (pH Ͻ 4.0), the upper temperature limit for photosynthetic-based primary production is ϳ56°C. Under these conditions, phototrophic activity is restricted to the unicellular eukaryotic red algae Cyanidium, Galdieria, and Cyanidioschyzon, collectively referred to as "cyanidia" (6,12,31,48). Primary production above this temperature in acidic environments occurs through chemoautotrophy, a metabolism restricted to prokaryotes.…”
Section: ؊1mentioning
confidence: 99%